UNDER THE LOCAL REGIME: CHAOS IN VILLAGE LAND MANAGEMENT SUBSEQUENT TO PRIVILEGE OF SPECIAL REGION OF YOGYAKARTA - Dominggus Ndou Baru; Fatih Gama Abisono Nasution (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
This research examines the management and utilization of village land in the Sriharjo Village. This research was conducted based on the problem that village authority was still hampered, impacting the Sriharjo Village’s government was not optimally managing and utilizing village land. The obstruction of village authority was stripped away by regulations from the Sultanate's authority. As a result, there were inconsistencies between Sriharjo Village rules and Sultanate regulations regarding the administration and use of village land. Although this behaviour is frequently observed in the villages of Special Region of Yogyakarta, few people have looked into, dissected, or even criticised this issue. This study aims to reveal how the Village Government responds to the dynamics of regime contestation. This research is a qualitative type with a descriptive method. Observation, interviews, and documentation are used as data gathering methods in Sriharjo Village, Kapanewon Imogiri, Bantul Regency. The study's findings shows that the administration and use of village land in the Sriharjo Village underwent a discourse that gave rise to the dynamics of competition between the Village Law regime and the Privileges Law regime of the Special Region of Yogyakarta. According to Article 76 paragraph (1) of Law Number 6 of 2014 concerning Villages, the Sultanate's authority's use of village land is contrary to village authority. It is evident that the Privileges Law regime weakens local authority while using village land. The Special Region of Yogyakarta Privileges Law, namely from Law No. 13 of 2012, is integrated with the Governor Regulation Number 34 of 2017 on the usage of village land. This study concludes that the administration and use of village land in Sriharjo Village led to a discourse of contestation between the Village Law regime and the Privileges Law regime, and it also resulted in a dualism of power, namely between the Village and the Sultanate.